The psychological impact of the coronavirus disease 2019 pandemic on women who become pregnant after receiving treatment for infertility: a longitudinal study - Alice D. Domar, Ph.D; Jaimin S. Shah, M.D; Annika Gompers, Ph.D; Alison J. Meyers, B.A; Darya R. Khodakhah; Michele R. Hacker, Sc.D; Alan S. Penzias, M.D; Denny Sakkas, Ph.D; Thomas L. Toth, M.D; Denis A. Vaughan, M.D (Elsevier, 2022)
Objective: To compare the impact of the coronavirus disease 2019 (COVID-19) pandemic on the psychological health of patients with infertility who have become pregnant with that of women who have not. Design: Prospective cohort study conducted from April 2020 to June 2020. The participants completed three questionnaires over this period. Setting: A single large, university-affiliated infertility practice. Patients: A total of 443 pregnant women and 1,476 women still experiencing infertility who completed all three questionnaires. Interventions: None. Main Outcome Measures: Patient-reported primary stressor over three months of the first major COVID-19 surge; further data on self-reported sadness, anxiety, loneliness, and the use of personal coping strategies. Results: Pregnant participants were significantly less likely to report taking an antidepressant or anxiolytic medication, were less likely to have a prior diagnosis of depression, were more likely to cite COVID-19 as a top stressor, and overall were less likely to practice stress-relieving activities during the first surge. Conclusions: Women who became pregnant after receiving treatment for infertility cited the pandemic as their top stressor and were more distressed about the pandemic than their nonpregnant counterparts but were less likely to be engaging in stress-relieving activities. Given the ongoing impact of the pandemic, patients with infertility who become pregnant after receiving treatment should be counseled and encouraged to practice specific stress-reduction strategies.